Variant of bone restoration in humeral nonunion with a free fibular autograft in the conditions of transosseous osteosynthesis - Sharof M. Davirov; Paizilla U. Urinbaev; Dzhalolidin Sh. Mansurov; Farrukh A. Gafurov; Dmitry Yu. Borzunov (Гений oртопедии)
Introduction Failures in surgical rehabilitation of patients with humeral fractures result in the formation of a multicomponent complex of pathological symptoms, including nonunion or bone defect, changes in the shape and length of humeral fragments, development of persistent angiotrophic disorders of the upper limb and contractures of the shoulder and elbow joints. Despite the effectiveness of using metal implants, there are risks in surgical osteosynthesis in complex anatomical and functional lesions. The purpose of the work was to demonstrate a new technology of bone plasty with free fragments of the fibula as a bone-plastic material for restoring the integrity of the humerus in bone nonunion and defects in the conditions of transosseous osteosynthesis and transosseous fixation of the grafts with wires. Materials and methods A free autograft of the fibula shaped as a cylindrical fragment, which was resected proximally to the ankle joint level at 8.0-9.0-cm distance, was used as a bone plastic material. The fibula graft was fragmented intraoperatively. Fragments were implanted along the periphery of the humerus fragments overlapping of the pseudarthrosis site. Free autografts of the fibula were transosseously fixed with wires. A wire/half-pine Ilizarov apparatus with three external supports was placed to fix the segment. Discussion The "gold standard" material for bone plasty is autogenous bone. If defects and pseudoarthroses of the humerus are located in the distal metaepiphysis, the application of the fibular cylinder-shaped fragment with intraosseous reinforcement of the humeral bone is technically difficult. Open co-aptation of the humeral fragments with adequate contact between them and application of the optimal autogenous bone-plastic material which overlaps the pseudarthrosis zone to increase the volume of bone mass ensure the restoration of bone regeneration in the pseudarthrosis zone. External fixation is optimal for fixation of bone fragments and grafts. Conclusion The originality of the developed technology lies in the use of several free bone autografts from the fibula implanted along the periphery of the humeral fragments junction. The area of active osteogenesis is thus created due to the combined effect of open co-aptation of the ends of the humeral fragments with resection of the endplates and bone autogenous grafts that overlap the problematic area. Additional transosseous fixation of bone autografts with wires ensures the stability of free grafts. Controlled fixation of humeral fragments with compression and adequate contact of the fragments is achieved with the Ilizarov apparatus.